The philosopher's "I" : autobiography and the search for the self - Wright, J. Lenore, 1972- (Albany, NY : State University of New York Press, 2006)
"This book examines philosophers' autobiographies as a genre of philosophical writing. Author J. Lenore Wright focuses her attention on five philosophical autobiographies: Augustine's Confessions, Descartes' Meditations, Rousseau's The Confessions, Nietzsche's Ecce Homo, and Hazel Barnes's The Story I Tell Myself. In the context of first-person narration, she shows how the philosophers in question turn their attention inward and unleash their analytical rigor on themselves."--Jacket
Writing the self -- Groundwork for a study of autobiography -- Writing the examined life -- The rationale for autobiographical writing -- Autobiography as confession -- Features of autobiographical writing -- Conclusions -- Bifurcating the self -- Self-ascription and self-description -- The inner self -- The outer self -- Conclusions -- Masking the self -- Deception and concealment -- Knowledge and truth in autobiography -- Self-deception -- Self-concealment -- Self-masking -- Conclusions -- Tranforming the self -- The dialectic of philosophical autobiography -- Interpretation and understanding -- Gracia on interpretation -- Gadamer on truth in interpretation -- Nietzsche and the subversion of the self.
Includes bibliographical references (pages 203-209) and index.
Print version record.
English.
JSTOR
Keywords: Philosophers -- Biography -- History and criticism; Autobiography; Philosophes -- Biographies -- Histoire et critique; Autobiographie; autobiography (genre); BIOGRAPHY & AUTOBIOGRAPHY -- Reference; Autobiography; Philosophers -- Biography; Criticism, interpretation, etc